2021
DOI: 10.1039/d1nr07104a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks/polydopamine synergistic interface enhancement of carbon fiber/phenolic composites for promoting mechanical and tribological performances

Abstract: Multiscale MOFs/PDA-enhanced carbon fiber/phenolic composites with rigid–flexible structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…The B1s analysis reveals that the B-O bonds become weakened after heat treatment at 300 °C (see Figure S2g,h ). From the TGA analysis and XPS analysis, we can deduce that carbon and nitride were formed during the heat treatment at 300 °C, which was also verified by contact angle measurements (see Figure S3 ) [ 6 ]. The samples with carbon and nitride possess excellent hardness but have a relatively low EIT (see Figure 12 ), which might cause them to easily peel off during sliding because of their brittle properties [ 34 ].…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The B1s analysis reveals that the B-O bonds become weakened after heat treatment at 300 °C (see Figure S2g,h ). From the TGA analysis and XPS analysis, we can deduce that carbon and nitride were formed during the heat treatment at 300 °C, which was also verified by contact angle measurements (see Figure S3 ) [ 6 ]. The samples with carbon and nitride possess excellent hardness but have a relatively low EIT (see Figure 12 ), which might cause them to easily peel off during sliding because of their brittle properties [ 34 ].…”
Section: Resultsmentioning
confidence: 65%
“…Many papers have reported that phenolic-matrix composites exhibit excellent synergistic effects on mechanical and tribological properties. Different reinforcements, such as glass fibers/fabric, carbon fibers [ 6 ], ceramic nanoparticles, graphene, and soft metals, have been used to promote tribological properties [ 7 , 8 ]. Suitable interfacial bonding, such as surface modification, including acid etching, plasma bombardment, and chemical grafting, is needed to improve the tribological properties of phenolic composites [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differ from S1, it could be observed in Figure 6b 1 that spherical silicone particles evenly distributed in the porous frame structure of the S2. These silicone particles benefited to establish numerous micro‐protrusions onto the surface of matrix, contributing to the formation of strong mechanical interlocks between modified fibers and the matrix 4 . After the in‐situ growth of SiO 2 , these core‐shell hybrids (silicone@SiO 2 ) facilitated fibers to interweave and form a complex network structure, 17,27 as exhibited in Figure 6c 1 .…”
Section: Resultsmentioning
confidence: 99%
“…28 From DTG curves, three decomposition peaks at 330-350 C, 450-490 C, and 550-580 C were observed in Figure 7b, corresponding to the thermal decomposition of cellulose fibers, polyimide resin and aramid fibers. 4 As displayed in Figure 7b, the typical peak of S3 shifted from 450 C to 476 C, indicating the silicone@-SiO 2 -modified resin matrix owned a greater resistance ability of thermal decomposition. Thus, the introduction of silicone@SiO 2 hybrids into the complex system of samples contributed to promoting the thermal stability of materials.…”
Section: Thermal Properties Of Paper-based Friction Materialsmentioning
confidence: 88%